SECONDARY PULMONARY ARTERIAL HYPERTENSION IN SYSTEMIC DISEASES OF CONNECTIVE TISSUE - N. A. Shostak; J. K. Novikov; A. L. Chernayev; A. A. Klimenko; P. V. Novikov (Столичная издательская компания, 2016)
Modern definition of pulmonary arterial hypertension (PAH) as well as data on prevalence and incidence of secondary PAH in systemic disease of connective tissue is presented,  including data of USA, France and Scotland registers. The main chains of pathogenesis, classification approaches, clinical features and diagnostics are described.